Art Therapy for Children in Short-Term Hospitalization - Meirav Hen (Continuity in Education, 2023)
Pediatric hospitalization is known to be associated with adverse developmental and psychosocial outcomes for young patients. Art therapy is a direct means of addressing the emotional world of the hospitalized child. However, the hospital setting sometimes requires adaptations of this practice to a short-term mode. To explore the characteristics of the adjusted short-term art therapy mode, 10 experienced art therapists who work with hospitalized children were interviewed. Results highlighted the unique aspects of working with children who enter short-term hospitalization, addressing the unknown but most likely brief duration of art therapy and the issues involved, such as the need to use problem-focused strategies, the diffused therapeutic space, interaction with a multidisciplinary staff, and parent’s presence during the therapy session. Integrating the principles of art therapy with the principles of short-term therapy, this paper explores a model for carrying out short-term art therapy with children undergoing short hospitalization.